Mapping the Research Landscape of SME Digitalization: A Bibliometric Analysis - Rizkita, Marsya Aulia; Fauzi, Muchamad Rizky; Nurrahma, Aisyah Asri; Hermawan, Agus; Handayati, Puji (Universitas Kadiri, 2025)
Small and Medium Enterprises (SMEs) are crucial drivers of national economies, particularly in developing countries like Indonesia. The COVID-19 pandemic significantly disrupted SME operations, yet also accelerated the adoption of digital technologies as a strategy for resilience and recovery. This study aims to map the research landscape of SME digitalization through a bibliometric analysis using data extracted from the Scopus database for the period 2020–2025. Employing a systematic literature review (SLR) and PRISMA methodology, 96 open-access articles in the field of Business, Management, and Accounting were selected and analyzed. The results reveal a sharp increase in digitalization-related research post-pandemic, with central themes including business models, sustainability, industry 4.0, and digital strategy. Network, overlay, and density visualizations generated via VOS viewer indicate that while digital transformation is a well-established topic, emerging themes such as digital maturity, governance, and internationalization present new research directions. This study contributes by offering a comprehensive overview of existing literature, highlighting conceptual linkages, and identifying future research avenues that integrate digital innovation, crisis resilience, and strategic development in SMEs.